Narrow row and crossed lines associated with different plant densities of soybean - Balbinot Junior, Alvadi Antonio (2015)
The spatial arrangement of soybean plants affects the intraspecific competition for light, water and nutrients, which can change the biomass production, incidence of pests, diseases and weeds, plant lodging, and grain yield. This work aimed to evaluate the agronomic performance under different row spacing, plant densities and crossed rows. Two field experiments were carried out in Campo Mourão, Paraná State, Southern Brazil, using the randomized complete block experimental design, in a 3x3x2 factorial arrangement, with four replications. The treatments were formed by the combination of three row spacings (0.30, 0.45, and 0.60 m), three plant densities (300,000; 450,000; and 600,000 plants ha-1), and two row design (crossed or parallel rows). For all variables, interaction of the experimental factors was not significant. The row spacing of 0.45 m provided the highest grain yield in relation to 0.30 and 0.60 m. The density of 300,000 plants ha-1 showed higher yield of soybeans in late sowing. The crossed lines did not increase the productive performance in soybean.